Green Economy Model Based on Islamic Boarding Schools: A Study of Waste Bank Management at the Blokagung Darussalam Islamic Boarding School, Banyuwangi - Fadlan Al-Ahmad Rausyan Fikri; Khoirunnisa Musari; Abdul Wadud (PT. Anagata Sembagi Education, 2025)
The waste problem is a national-level issue, affecting all layers of society. Handling, managing, and utilizing waste must be continuously pursued to minimize the emergence of other problems. For this reason, green economy is one of the appropriate solutions to address waste problems. This is based on its five principles: sustainability, welfare, justice, planetary boundaries, and inclusivity. With these principles, green economy does not exploitatively eliminate waste without processing it, but instead, waste is processed, reused, and empowered to have economic value. With the Green Economy Index released by the National Development Planning Agency (Bappenas/PPN), it is expected that green economy can be realized in all environments, including in Islamic boarding schools. Through the empowerment of waste banks at Darussalam Islamic Boarding School in this study, it is expected that other Islamic boarding schools can also apply good waste management models and implement green economy in their environment. This study aims to deeply examine the green economy model in Islamic boarding schools through waste bank programs. This study uses a qualitative approach, conducting direct observations at Darussalam Islamic Boarding School. The results show a good potential for applying green economy in Islamic boarding schools through waste banks and waste management. This also indicates that the scope of green economy is not limited to specific conditions or regions. The key aspect of successful green economy implementation is direct action, not just rhetoric. The obstacles found in this study are the lack of awareness among students in maintaining environmental cleanliness and many students still rely on others for waste management and waste banks.